An Online Physics Laboratory Delivered Through Live Broadcasting Media: A COVID-19 Teaching Experience - Setiaji, Bayu; Santoso, Purwoko Haryadi (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2023)
The COVID-19 pandemic has constituted a sudden educational transformation around the world. It has disrupted instructors, including physics educators, forcing them to adjust to remote teaching. The hands-on laboratory, one of the components of physics instruction, has also had to rapidly go online in all branches of this science, including nuclear physics. In this study, live broadcasting media was designed to conduct a remote nuclear physics laboratory. We then evaluated the immediate impact of this new mode of lab instruction on students’ learning and attitude toward this type of instruction. Fifty-nine 3rd-year physics students at a public university in Indonesia participated in this study. The effectiveness of instruction was examined by analyzing both weekly reports and open-ended responses about students’ learning experiences. In summary, it was evident that live broadcasting media was an effective way to conduct an online nuclear physics laboratory. Accordingly, students’ attitudes demonstrated constructive behaviors about their remote laboratorial experiences. Our findings imply that online platforms are one way to offer the physics laboratory during unanticipated transitions such as the COVID-19 pandemic. Students’ preference for a hands-on laboratory and the technical issues reported during the broadcasting session should be further examined to help design a remote nuclear physics laboratory that is even more accessible and enjoyable.